Organic Electrochemical Transistors/SERS-Active Hybrid Biosensors Featuring Gold Nanoparticles Immobilized on Thiol-Functionalized PEDOT Films - Chou, Jia-An; Chung, Chieh-Lin; Ho, Po-Cheng; Luo, Chun-Hao; Tsai, Yu-Han; Wu, Chung-Kuan; Kuo, Chiung-Wen; Hsiao, Yu-Sheng; Yu, Hsiao-hua; Chen, Peilin (Frontiers in Chemistry, 2019)
In this study we immobilized gold nanoparticles (AuNPs) onto thiol-functionalized poly(3,4-ethylenedioxythiophene) (PEDOT) films as bioelectronic interfaces (BEIs) to be integrated into organic electrochemical transistors (OECTs) for effective detection of dopamine (DA) and also as surface-enhanced Raman scattering (SERS)–active substrates for the selective detection of p-cresol (PC) in the presence of multiple interferers. This novel PEDOT-based BEI device platform combined (i) an underlying layer of polystyrenesulfonate-doped PEDOT (PEDOT:PSS), which greatly enhanced the transconductance and sensitivity of OECTs for electrochemical sensing of DA in the presence of other ascorbic acid and uric acid metabolites, as well as amperometric response toward DA with a detection limit (S/N =3) of 37 nM in the linear range from 50 nM to 100 M; with (ii) a top interfacial layer of AuNP-immobilized three-dimensional (3D) thiol-functionalized PEDOT, which not only improved the performance of OECTs for detecting DA, due to the signal amplification effect of the AuNPs with high catalytic activity, but also enabled downstream analysis (SERS detection) of PC on the same chip. We demonstrate that PEDOT-based 3D OECT devices decorated with a high-density of AuNPs can display new versatility for the design of next-generation biosensors for point-of-care diagnostics.